HISTORY OF PEDIATRICS - SUMMARY OF THE PAST AND FUTURE PERSPECTIVE - G.L. Mikirtuichan; V.Yu. Albitsky ("Paediatrician" Publishers LLC, 2006)
(Voprosy Sovremennoi Pediatrii = Current Pediatrics 2006;5(2):78-79)